Standards of In-Patient Medical Seclusion Reviews - Mohammed Murtza; Taha Anjum (BJPsych Open, 2024)
Aims Seclusion is a method used by mental health teams around the world to manage aggressive and disturbed behaviour in psychiatric patients in situations where there is immediate risk of harms to others. A quality improvement project was carried out over two hospital in-patient sites containing 6 wards to see if seclusion reviews were completed safely and documented appropriately according to the guidelines set out by South West Yorkshire Mental Health Trust and the Royal College of Psychiatrists.